2014
DOI: 10.1038/ejhg.2014.157
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and genetic analysis of multiple primary cancer referrals to genetics services

Abstract: Multiple primary malignant tumours (MPMT) are frequently taken as an indicator of potential inherited cancer susceptibility and occur at appreciable frequency both among unselected cancer patients and, particularly, among referrals to cancer genetics services. However, there is a paucity of information on the clinical genetic evaluation of cohorts of MPMT patients representing a variety of tumour types. We ascertained a referral-based series of MPMT cases and describe the patterns of tumours observed. Service-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…17,18 In addition, a retrospective study of individuals with multiple primary malignancies who were referred for clinical genetic testing found that 44 of 111 individuals (39.6%) carried a variant in 1 cancer predisposition genes, with DNA mismatch repair genes among the most frequently mutated. 19 Although the presence of certain constellations of MPMNs in a single individual is considered to be one indication for referral for genetic risk assessment, to the best of our knowledge the percentage of individuals with MPMNs who are referred for genetic assessment and the outcomes of clinical genetics referrals in these patients with multiple primary cancers has not been extensively described.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In addition, a retrospective study of individuals with multiple primary malignancies who were referred for clinical genetic testing found that 44 of 111 individuals (39.6%) carried a variant in 1 cancer predisposition genes, with DNA mismatch repair genes among the most frequently mutated. 19 Although the presence of certain constellations of MPMNs in a single individual is considered to be one indication for referral for genetic risk assessment, to the best of our knowledge the percentage of individuals with MPMNs who are referred for genetic assessment and the outcomes of clinical genetics referrals in these patients with multiple primary cancers has not been extensively described.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant correlation was identified for younger age at first tumor diagnosis, PGL, renal oncocytoma or malignant PGL, and the identification of a genetic mutation ( P > 0.05 for all associations). The mean MTS ( 11 ) value in group A patients with a mutation was 3.6 compared with 1.8 in those without a mutation ( P = 0.09).…”
Section: Resultsmentioning
confidence: 82%
“…Although the literature review identified patients with non-VHL RAPTAS and a germline mutation had relatively young-onset PC/PGL/HNPGL (mean, 31.8. years; RCC, 41.4 years) in the case series, there was no clear relationship between age at tumor diagnosis and presence/absence of a mutation. Although the difference in MTS ( 11 ) between mutation-positive and mutation-negative cases did not reach statistical significance, further studies are required to determine MTS utility in group A RAPTAS cases. Although RAPTAS might in some cases arise coincidentally, we note in two SDHB mutation-positive cases in our series (probands 9 and 18), age at tumor diagnosis was 60 years or older.…”
Section: Discussionmentioning
confidence: 88%
“…During gene expression-based cancer diagnosis, in addition to finding the subset of potential genes causing the cancer, the researcher is expected to trace out the physiognomies of the causative genes in terms of their part in multiple cancer classes [57]. The GO Sim package in the R platform [22] was used to compute the similarity value for the genes identified in the GCM_RM dataset using the GO terms.…”
Section: Resultsmentioning
confidence: 99%